In silico modeling revealed new insights into the mechanism of action of enzyme 2'-5'-oligoadenylate synthetase in cattle. Issue 24 (26th December 2022) - Junghare, Vivek; Alex, Rani; Baidya, Apoorva; Paul, Manish; Alyethodi, Rafeeque R.; Sengar, Gyenaendra Singh; Kumar, Sushil; Singh, Umesh; Deb, Rajib; Hazra, Saugata
Abstract: The innate immune system has an important role in developing the initial resistance to virus infection, and the ability of oligoadenylate synthetase to overcome viral evasion and enhance innate immunity is already established in humans. In the present study, we have tried to explore the molecular and structural variations present in Sahiwal (indigenous) and crossbred (Frieswal) cattle to identify the molecular mechanism of action of OAS1 gene in activation of innate immune response. The significant changes in structural alignment in terms of orientation of loops, shortening of β-sheets and formation of 3–10 α-helix was noticed in Sahiwal and Frieswal cattle. Further, it has been observed that OAS1 from Sahiwal had better binding with APC and DTP ligand than Frieswal OAS1. A remarkable change was seen in orientation at the nucleoside base region of both the ligands, which are bound with OAS1 protein from Frieswal and Sahiwal cattle. The Molecular Dynamic study of apo and ligand complex structures was provided more insight towards the stability of OAS1 from both cattle. This analysis displayed that the Sahiwal cattle protein has more steady nature throughout the simulation and has better binding towards Frieswal in terms of APC and DTP binding. Thus, OAS1 protein is the potential target for explaining the innate immune response in Sahiwal than Frieswal. Communicated by Ramaswamy H. Sarma